Development of As(III) and Hg(II) sensors utilizing amino acids and peptides as recognition elements - Daud, Nurulhaidah (2012)
Toxic metal ions in waste water such as arsenic and mercury have lethal effects on the environment and living organisms. This indicates several striking requirements for novel analytical technologies that are fast, portable and cost-effective. In this work, sensitive voltammetric methods for the detection of arsenic and mercury ions are developed based on modified platinum and gold electrode, respectively. The electrochemical sensors that comprise of metal chelating reagents, together with an ion carrier immobilised within polymeric thin films such as Nafion were developed. The molecule receptors such amino acids (glutamine and leucine) are used for the determination of As(III) ion in water samples using the voltammetric technique. Determination of As(III) by using CNTs/glutamine/Nafion modified platinum electrode was found to be reproducible with R.S.D of 7.3%. The redox peak current of As(III) shows a linear response towards different concentrations of As(III) and linear calibration curves were obtained in the range of 0.1×10-8 to 50.5×10-8 M. The sensitivity is 1×10-4 AμM-1 with the limit of detection 3.63×10-8 M which is better, compared to CNTs/leucine/Nafion modified Pt electrode in thedetermination of As(III). The LOD reported here is well within the range defined by the WHO regulation (10 μgL-1). The determination of As(III) by using CNTs/leucine/Nafion modified Pt electrode has optimum response, observed at pH 5 with R.S.D. of 7.6%. The redox peak current of As(III) shows a linear response towards different concentrations of As(III) and linear calibration curves were obtained in the range of 0.02 μM to 2 μM. The limit of detection was determined as 1.67×10-8 M and the sensitivity recorded to be 2.1×10-5 AμM-1. A novel sensing strategy, based on the SAM method of MPA-HFHAHFAF peptide and Biotinyl Somatostatin-14 peptide has been used as a receptor for the determination of Hg(II) ion using gold electrode. The reproducibility of MPAHFHAHFAF peptide modified gold electrode is 4.5%, indicating a reproducible and reliable detection system. A linear working range for the detection of mercury was obtained between 51 to 161 μgL-1 with LOD of 1.9 μgL-1. The LOD obtained was below than the WHO guidelines for drinking water of 2 μgL-1. The detection of mercury using Biotinyl Somatostatin-14 peptide /Nafion had been carried out under acidic conditions. Good relative standard deviation of 3.7% was obtained. A linear calibration plot in the range of 40-170 μgL-1 was obtained with the sensitivity value of 1×10-10 AμM-1. The value of LOD obtained was below WHO guidelines for drinking water, 0.4 μgL-1. In terms of the LOD value, the Biotinyl Somatostatin-14 peptide /Nafion peptide modified gold electrode was better compared to the MPAHFHAHFAF peptide modified gold electrode for determining Hg(II).